Analysis of phase composition of LiZn and LiTi ferrites by XRD and thermomagnetometric analysis; Journal of Magnetism and Magnetic Materials; Vol. 465 - Lysenko E. N. Elena Nikolaevna; Astafyev A. L. Alexander Leonidovich; Vlasov V. A. Vitaliy Anatolievich; Surzhikov A. P. Anatoly Petrovich (2018, 2018)
Title screen